Quality of life and its predictors among breast cancer patients treated with surgery—a retrospective minimum 3-year follow-up study - Tang, Wen-Zhen; Lu, Yao-Qiong; Zhu, Sheng-Rui; Teng, Yan-Juan; Wei, Tian-Fu; Chen, Guo-Lian; Jia, Kui (Frontiers in Oncology, 2024)
AimQuality of life (QoL) has been identified as an important indicator of positive outcomes among breast cancer (BC) survivors. However, the status and predictors of QoL in China remain unclear. This retrospective follow-up study aimed to examine the QoL levels among BC patients following surgery and to assess the influence of sociodemographic, clinical, and psychological factors on QoL.MethodsAn institution-based retrospective follow-up study was conducted among 714 BC patients who received surgery at the First Affiliated Hospital of Guangxi Medical University between January 2016 and December 2019. Our primary outcome measure was QoL, assessed using the European Organization for Research and Treatment of Cancer QoL Questionnaire Core 30 (EORTC QLQ-C30). Anxiety and depression were evaluated by the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS), respectively. Data on the patient demographics and clinical were derived from medical records. Results are presented as means (SD), medians [Q1, Q3], or percentage (%). We used R 4.2.2 software to identify factors associated with QoL after BC surgery. AMOS 28.0 was used to construct a structural equation model (SEM) to predict QoL outcomes.ResultsThe overall QoL score was 43.30 ± 4.77 (mean ± SD). Predictive factors were: surgery type, radiotherapy, anxiety, and depression (p<0.05). The results of the SEM indicated that anxiety and depression had a direct negative effect on QoL (effect value was -0.46, -0.84, respectively, p<0.05), radiotherapy had a direct positive effect on QoL (effect value was 0.71, p<0.05). The type of surgery (mastectomy) impacted QoL both directly and indirectly through its association with depression, with direct and indirect effect values of -0.96 and -0.66, respectively (p < 0.05).ConclusionThe QoL of BC patients after surgery is generally moderate to low. Medical staff should prioritize early identification and rehabilitation management for patients experiencing anxiety, depression, radiotherapy, and mastectomy to enhance their QoL. Our findings provide a strong foundation for developing nursing intervention plans and assessment guidelines for practitioners caring for BC patients.